Studi Etnobotani: Inventarisasi dan Pemanfaatan Tumbuhan Obat di Desa Pelabai Kabupaten Lebong, Provinsi Bengkulu - Safniyeti, Safniyeti; Astuti, RR Sri; Fatimatuzzahra, Fatimatuzzahra; Kasrina, Kasrina; Nugraha, Fadel (Mahesa Research Center, 2025)
Traditional medicinal plants hold a crucial role in public health in rural areas where medical facilities are limited. People often rely on plants as medicinal raw materials. This study aims to investigate ethnobotany and inventory the types of medicinal plants used by the residents of Pelabai Village, Lebong Regency, Bengkulu Province. Data were collected through interviews using snowball sampling and analyzed desriptively. Semi-structured interviews with open-ended questions and direct observations of daily activities were conducted. Twenty respondents who knew, understood, and used plants as alternative medicine were selected. The study identified 30 plant species in the village used for traditional medicine. Leaves were the most commonly used plant part for medicinal purposes (76.67%), followed by stems (23.33%), rhizomes (13.33%), roots (10%), sap (6.67%), and other parts such as gel, flowers, fruit, and stem bark (3.33%). The plants were prepared for medicinal use through boiling, mashing, grating, dripping, squeezing, sticking, chewing, or direct consumption. Plant were used to treat various minor ailments including nausea, aches, skin diseases, beauty enhancement, respiratory issues, cholesterol, and hypertension.